Gene Action and Combining Ability Analysis in Brinjal (Solanum melongena L.) - S Ramesh Kumar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2013)
Combining ability analysis in brinjal genotypes indicated significant genotypic and environmental variations for all the 15 characters studied. Both general combining ability (GCA) and specific combining ability (SCA) variances showed significant interactions. Genotypes Palamedu Local (L5), Alagarkovil Local (L4), Melur Local (L6) and Annamalai (T1) were found to be good general combiners, and the crosses L3 x T3 (Kariapatty Local x Punjab Sadabahar), L8 x T1, (Nilakottai Local x Annamalai), L4 x T1 (Alagarkovil Local x Annamalai), L6 x T2 (Melur Local x KKM 1), L7 x T3 (Keerikai Local x Punjab Sadabahar) and L7 x T2 (Keerikai Local x KKM 1) were identified as good specific combiners for fruit yield and other related traits. These hybrid combinations can be used for commercial exploitation for fruit yield in brinjal.